An Interactive Web Tool for Facilitating Shared Decision-Making in Dementia-Care Networks: A Field Study - Span, Marijke; Smits, Carolien; Jukema, Jan; Groen-van de Ven, Leontine; Janssen, Ruud; Vernooij-Dassen, Myrra; Eefsting, Jan; Hettinga, Marike (Frontiers in Aging Neuroscience, 2015)
Background An interactive web tool has been developed for facilitating shared decision-making in dementia-care networks. The DecideGuide provides a chat function for easier communication between network members, a deciding together function for step-by-step decision-making, and an individual opinion function for eight dementia-related life domains. The aim of this study was to gain insight in the user friendliness of the DecideGuide, user acceptance and satisfaction, and participants’ opinion of the DecideGuide for making decisions. Materials and methods A 5-month field study included four dementia-care networks (19 participants in total). The data derived from structured interviews, observations, and information that participants logged in the DecideGuide. Structured interviews took place at the start, middle, and end of the field study with people with dementia, informal caregivers, and case managers. Results 1. The user friendliness of the chat and individual opinion functions was adequate for case managers and most informal caregivers. Older participants, with or without dementia, had some difficulties using a tablet and the DecideGuide. The deciding together function does not yet provide adequate instructions for all. The user interface needs simplification. 2. User acceptance and satisfaction: everybody liked the chat’s easy communication, handling difficult issues for discussion, and the option of individual opinions. 3. The DecideGuide helped participants structure their thoughts. They felt more involved and shared more information about daily issues than before. Conclusion Participants found the DecideGuide valuable in decision-making. The chat function seems powerful in helping members engage with one another constructively. Such engagement is a prerequisite for making shared decisions. Regardless of participants’ use of the tool, they saw the DecideGuide's added value.